Antimicrobial activity of citric acid functionalized iron oxide nanoparticles –Superparamagnetic effect. Issue 8 (1st June 2020) - Khan, Sidra; Shah, Zaheer H.; Riaz, Saira; Ahmad, Naveed; Islam, Shumaila; Raza, M. Akram; Naseem, Shahzad
Abstract: Magnetic nanoparticles offer several advantages for various applications including biomedical. However, the surface of nanoparticles must be functionalized. For biocompatibility of magnetic nanoparticles, they must possess superparamagnetic behavior with high saturation magnetization (Ms ). For this purpose, we here report an application-oriented sol-gel route for the synthesis of iron oxide nanoparticles i.e. magnetite (Fe3 O4 ). These magnetic nanoparticles are functionalized by different concentrations of citric acid such as 0.1 M, 0.2 M, 0.3 M, 0.4 M and 0.5 M. Typically, citric acid gets adsorbed on the surface of nanoparticles with one or two carboxylate groups leaving at least one carboxylic acid group on the surface making them hydrophilic to prevent agglomeration that allows conjugation with specific drugs. XRD results confirm the magnetite phase of iron oxide nanoparticles (un-functionalized). Magnetite phase and maghemite phase are observed within different concentrations 0.1 M, 0.2 M, 0.4 M and 0.5 M of citric acid functionalized iron oxide nanoparticles. FTIR analysis confirms the attachment/capping of citric acid on nanoparticles' surface through the band 1710 cm −1 corresponding to CO of COOH group. Moreover, Raman analysis confirms the presence of characteristic band at 670 cm −1 attributed to Fe3 O4 (Magnetite). Particle size analyzer indicates the hydrodynamic diameter size of ~25 nm after 0.3 M citric acid functionalized nanoparticles and zeta-potential analysis also confirms the functionalization of nanoparticles with citric acid. Citric acid functionalized nanoparticles show superparamagnetic behavior with saturation magnetization of 85emu/g (citric acid concentration 0.3 M). Magnetic properties are also studied at low temperatures (5K–300K at Max. field 50 KOe) to confirm the presence of superparamagnetic behavior with negligible coercivity (Hc ) and increased saturation magnetization (100emu/g at 5K). 0.3 M citric acid functionalized nanoparticles (magnetite, superparamagnetic) appeared to be beneficial for antibacterial activity with zone of inhibition of 36 mm. The experimental analyses confirm that 0.3 M citric acid functionalized nanoparticles are promising candidate for biomedical applications. Highlights: Citric acid (CA) functionalized magnetite nanoparticles (MNPs) were synthesized by low-temperature sol-gel method. XRD results indicated the formation of magnetite (Fe3 O4 ) phase at 0.3 M citric acid concentration. FTIR bands of C–O and C=O, from citric acid, indicated successful attachment of functional groups on MNPs surface. 0.3 M functionalized MNPs resulted in high saturation magnetization of 85 emu/g with size less than 25 nm. 0.3 M CA functionalized MNPs proved to be successful candidate as antibacterial agent with zone of inhibition 36 mm.